Wake up, I'm fat! - Manheim, Camryn (New York : Broadway Books, 1999)
The Emmy award-winning actress from ABC's "The practice" shares her sassy, refreshingly smart take on the trials and tribulations of being overweight.
Keywords: Manheim, Camryn; Actors -- United States -- Biography